DEKONSTRUKSI TAFSIR BIAS GENDER: KRITIK FEMINISME TERHADAP POLIGAMI DALAM KITAB TAFSIR INDONESIA - Zul Erpan Qurniawan (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2025)
This study critically examines gender bias in the interpretation of Qur'an Surah An-Nisa verse 3 by analyzing eight classical Indonesian tafsir (exegesis) texts. Employing a qualitative content analysis approach, the research uncovers how patriarchal ideology has historically shaped the understanding of polygamy within these interpretations. The findings indicate that many classical scholars framed polygamy in ways that subordinate women, often portraying them as passive recipients of male authority. Common justifications for polygamy—such as a wife’s infertility, disobedience, or inability to fulfill marital obligations—are shown to stem not from the Qur’anic text itself but from prevailing cultural norms and patriarchal assumptions. These interpretations, while influential, often overlook the ethical and egalitarian spirit of the Qur’an, particularly its emphasis on justice and compassion. The study calls for a re-evaluation of such interpretations through a contemporary lens that prioritizes contextual understanding and gender equity. By advocating for a justice-oriented hermeneutic, this research contributes to the broader discourse on Islamic reform and gender justice. It emphasizes the need for interpretations that reflect the Qur’an’s core values of fairness, dignity, and humanity, thereby promoting a more inclusive and balanced view of women’s roles in modern Muslim societies